Structural characterisation of Cu2.04Zn0.91Sn1.05S2.08Se1.92. Issue 6 (22nd April 2015) - Gurieva, G.; Dimitrievska, M.; Zander, S.; Pérez‐Rodríguez, A.; Izquierdo‐Roca, V.; Schorr, S.; Tsuboi, Nozomu; Wakita, Kazuki; Yamada, Akira; Shirakata, Sho; Wada, Takahiro; Niki, Shigeru; et al.
Abstract Quaternary Cu2ZnSn(S1‐xSex)4 compounds are promising semiconductor materials for absorber layer in thin film solar cells. Record efficiency devices (12.6%) exhibit an off‐stoichiometric composition of the absorber layer. These deviations from stoichiometry cause intrinsic point defects, which determine the electronic properties of the semiconductor significantly. A structural analysis of a nearly C‐type off‐stoichiometric Cu and Sn rich and Zn poor Cu2ZnSn(S1‐xSex)4 mixed crystal with x=0.48 by a neutron diffraction investigation was performed. The average neutron scattering length method was applied, showing that the mixed crystal adopts the kesterite type structure. A detailed cation distribution analysis revealed the occurrence of ZnCu(2a) and SnZn anti‐site point defects additional to the Cu‐Zn disorder in the planes at z=1/4 and 3/4. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)